Two new species of the genus Anthaxia (Anthaxia Eschscholtz 1829) from China, and notes on the related species (Coleoptera: Buprestidae: Anthaxiini) - Bílý, Svatopluk (Zootaxa, 2015)
Anthaxia (Anthaxia) kmoniceki sp. nov. and Anthaxia (Anthaxia) ungulata sp. nov. (China, Sichuan) both belonging to the A. (A.) nitidula Linnaeus, 1758 species-group are described, illustrated and compared with the most similar species. A short description of the male and new records of Anthaxia (A.) nitiduliformis Bílý, 1995 are given together with the notes on the bionomy of the species-group.